An Integrated Approach of QTL Mapping and Genome-Wide Association Analysis Identifies Candidate Genes for Phytophthora Blight Resistance in Sesame (Sesamum indicum L.) - Asekova, Sovetgul; Oh, Eunyoung; Kulkarni, Krishnanand P.; Siddique, Muhammad Irfan; Lee, Myoung Hee; Kim, Jung In; Lee, Jeong-Dong; Kim, Minsu; Oh, Ki-Won; Ha, Tae-Joung; Kim, Sung-Up; Cho, Kwang-Soo (Frontiers in Plant Science, 2021)
Phytophthora blight (PB) caused by Phytophthora nicotianae is highly destructive disease in sesame (Sesamum indicum L.) In this study, we used linkage mapping and genome-wide association study (GWAS) to identify quantitative trait loci (QTL) and candidate genes associated with PB resistance. The QTL mapping in 90 RILs of the cross Goenbaek × Osan cross using genotyping-by-sequencing (GBS)-based single nucleotide polymorphism (SNPs) detected significant QTLs for PB resistance on chromosome 10, explaining 12.79%–13.34% of phenotypic variation. Association of this locus to PB resistance was also revealed through bulked segregant analysis in second RIL population (Goenbaek × Milsung cross) comprising 188 RILs. The GWAS of 87 sesame accessions evaluated against three P. nicotianae isolates identified 29 SNPs on chromosome 10 significantly associated with PB resistance. These SNPs were located within a 0.79 Mb region, which co-located with the QTL intervals identified in RIL populations, and hence scanned for identifying candidate genes. This region contained several defense-related candidate R genes, five of which were selected for quantitative analysis. One of these genes, SIN_1019016 was found to show significantly higher expression in the resistant parent compared to that in the susceptible parents and selected RILs. Paired-end sequencing of the gene SIN_1019016 in parental cultivars revealed two synonymous SNPs between Goenbaek and Osan in exon 2 of coding DNA sequences. These results help pinpoint SIN_1019016 as one of the candidate gene conferring PB resistance in sesame. These findings can facilitate the marker-assisted selection as well as the functional analysis of PB resistance candidate gene(s) in sesame.